Analyzing grain market efficiency in developing countries: review of existing methods and extensions to the parity bounds model - Negassa, Asfaw; Myers, Robert J.; Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 2003)
This paper discusses a modeling approach that extends and improves the standard parity bounds model (PBM) of spatial market efficiency by analyzing the dynamic effects of marketing policy changes. The model facilitates an improved understanding of the patterns of adjustment in grain marketing efficiency in response to policy changes in two main ways. First, it identifies whether there are statistically significant structural changes in trading regime probabilities as a result of a given marketing policy change. Second, it determines the time path of the response of spatial grain market efficiency to marketing policy changes, thus addressing the issue of how long will it take before the full effect of marketing policy change is realized on spatial grain market efficiency." -- from Abstract